Lineage-specific genes are prominent DNA damage hotspots during leukemic transformation of B-cell precursors - Boulianne,B; Robinson,ME; May,PC; Castellano,L; Blighe,K; Thomas,J; Reid,A; Muschen,M; Apperley,JF; Stebbing,J; Feldhahn,N (Cell Reports, 2017)
In human leukemia, lineage-specific genes represent predominant targets of deletion, with lymphoid-specific genes frequently affected in lymphoid leukemia and myeloid-specific genes in myeloid leukemia. To investigate the basis of lineage-specific alterations, we analyzed global DNA damage in primary B-cell precursors expressing leukemia-inducing oncogenes by ChIP-Seq. We identified >1000 sensitive regions, of which B-lineage-specific genes constitute the most prominent targets. Identified hotspots at B-lineage genes relate to DNA-DSBs, affect genes that harbor genomic lesions in human leukemia, and associate with ectopic deletionin successfully transformed cells. We further show that mostidentified regions overlap with gene bodies of highly expressed genes, and that induction of a myeloidlineage phenotype in transformed B-cell precursors promotes de novoDNA damage atmyeloid loci. Hence, we demonstrate thatlineage-specific transcriptionpredisposeslineage-specificgenes in transformed B-cell precursorsto DNA damage, whichis likely to promote the frequent alteration oflineage-specific genes in human leukemia.